THE EFFECT OF MODEL COLLABORATIFE LEARNING ASSISTED BY MEDIA BIG BOOK TO WRITING NARRATIVE SKILLS TO PRIMARY SCHOOL STUDENT (International Conference on Elementary Education, 2018)
Learning to write in elementary school needs to get serious attention. This results in low interest in students' reading and writing. This study aims to find out how much influence the collaborative learning model is assisted by the big book media on the skills of narrative essay writing in fourth grade elementary school students. The research method used is quantitative research with a type of pre-experimental research with the design of one shot case study. The research subjects in this study were fourth grade students of Matla'ul Khoiriah Elementary School, totaling 26 students and one teacher as active participants. The results showed hypothesis testing using one sample t-test which shows the results output data which can be analyzed that the amount of data as many as 26 students produce an average of 68.26 and testing hypothesis showed that the hypothesis is not accepted. This means that the average score of students is less than the Indonesian learning value minimal which is 72. It can be concluded that the collaborative learning model assisted by the big book media does not affect the narrative essay writing skills of the fourth grade students of elementary school. Nevertheless, the teacher and students gain learning experience by applying collaborative learning models assisted by the big book media namely narrative essay writing skills. Especially for teachers to gain experience assessing analytical narrative essays with five aspects, namely content, organization, vocabulary, language use and mechanics.